PENGARUH LIKUIDITAS, SOLVABILITAS, AKTIVITAS, DAN PROFITABILITAS TERHADAP LABA PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI - Risna, Risna (LPPM Institut Pendidikan Nusantara Global, 2023)
This research aims to determine the effect of liquidity, solvency, activity and profitability on profits in mining companies listed on the Indonesia Stock Exchange for the period 2012 to 2018. The sampling method was carried out using the purpose sampling method, and based on predetermined criteria, the number of samples was as large as 35 samples of mining companies active during the period 2012 to 2018. Hypothesis testing using multiple linear regression analysis with SPSS application tools. The results of this research show that the liquidity ratio has no significant effect on profits, the solvency ratio has a significant effect on profits, the activity ratio has a significant effect on profits, and the profitability ratio has a significant effect on profits.